Aggregate Earnings and Asset Prices - BALL, RAY; SADKA, GIL; SADKA, RONNIE (Journal of Accounting Research, 2009)
ABSTRACT A principal‐components analysis demonstrates that common earnings factors explain a substantial portion of firm‐level earnings variation, implying earnings shocks have substantial systematic components and are not almost fully diversifiable as prior literature has concluded. Furthermore, the principal components of earnings and returns are highly correlated, implying aggregate earnings risks and return risks are related. In contrast to previous studies, the correlation we report between the systematic components of earnings and returns is stable over time. We also show that the earnings factors are priced, in the sense that the sensitivities of securities' returns to the earnings factors explain a significant portion of the cross‐sectional variation in returns, even controlling for return risk. This suggests earnings performance is an underlying source of priced risk. Our evidence that the information sets of returns and earnings are jointly determined implies cash flow risk and return risk are not fully separable, and raises the possibility that it is the common variation of earnings and returns that is priced.